Scaffolding in learning to write: A focus on learners and teacher in rural area (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
This study focuses on rural area learners learning process, and the teachers roles in developing the rural learners writing skills. Specifically, this study aims to investigate how teacher assists the students in learning to write, and following that, this study then aims to understand how teachers assistance affects students writing skills. The participants of this study consisted of three fourth former students and their English teacher. In order to gather information about the teachers assistance and its effect on learners writing skills, two types of data were collected. Firstly, non-participant classroom observation was carried out for six months where the researcher observed and recorded each activity in the classroom. Secondly, all of the students written works during each activity were compiled and the content was analyzed to see the changes. One essay entitled My father will be used for the discussion of this paper. Finding showed that students managed to improve their sentences in the essay once the teacher assisted them through class discussion and individual comments.